Preliminary flagellin gene transfection into tumor cells - attempts of generating anti-tumor response in experimental model - Wędrowska, Ewelina; Wojciechowska, Marzena; Goede, Arkadiusz; Wędrowski, Mateusz; Waśniowski, Paweł; Chmielarski, Maciej; Piskorska, Elżbieta; Żukow, Walery (Journal of Education, Health and Sport, 2017)
The development of new research techniques, especially molecular ones, creates hopes for improved treatment efficacy and a better prognosis in lung cancer. The starting point for very important experiments in the field of immunotherapy is the sensitization of the immune system to the tumor antigen. The aim of the study was to determine whether using flagellin can induce innate antitumor effective, and thus, increase the immunogenicity of the tumor. The test material was the established mouse cell line LLC, derived from Lewis lung cancer. Vectors were constructed by cloning FliC inserts into the pCDH-MSC-T2A Puro plasmid. The cells were transfected directly and indirectly (with pseudoviruses, produced by previously transfected packaging cells HEK 293T). The transfection efficiency was confirmed by RT-PCR. The cells thus prepared were implanted subcutaneously in mice. The control group received non-transfected LLC cells. Then, after 6 weeks, the mice were scarified. The animals were sectioned to isolate the tumor and lungs in which the presence or absence of metastases was assessed. In mice that received immunotherapeutic vaccines containing transfected LLC cells, less tumor mass was found or a complete lack of it, and the lifespan was noticeably prolonged. In addition, no metastases occurred in the group vaccinated with cells transfected with direct technique. It can be concluded that flagellin is effective as an adjuvant in the process of presenting tumor antigens to T cells Thus, in the light of recent studies and reports, it is likely that in this experiment effectively increased immunogenicity of the tumor. Activating anti-tumor cellular responses using flagellin is a promising target for lung cancer immunotherapy.